Synthesis of bilocularin A carbamate derivatives and their evaluation as leucine transport inhibitors in prostate cancer cells. (November 2020) - Huxley, Cohan; Wibowo, Mario; Lum, Kah Yean; Gordon, Shelly; D'Hyon, Sebastian; Guan, Hanyu; Wang, Xueyi; Chen, Yuxi; Si, Mingran; Wang, Mengchao; White, Jonathan M.; Wahi, Kanu; et al.
Abstract: Large-scale extraction of the leaves of the Australian rainforest tree Maytenus bilocularis followed by extensive purification studies afforded the targeted and abundant dihydro- β -agarofuran, bilocularin A, in sufficient quantities (>500 mg) for detailed semi-synthetic chemistry. Eight bilocularin A carbamate analogues were synthesised using a series of commercially available isocyanate reagents in high purity (>95%) and variable yields (9–91%). All previously undescribed analogues were spectroscopically characterised using NMR, UV, IR and MS data. One compound afforded crystalline material and subsequent single crystal X-ray analysis (Cu-K α ) confirmed the chemical structure along with the absolute configuration. All compounds were evaluated for anti-proliferative activity against the human prostate cancer cell line LNCaP; none of the compounds showed significant (>50%) growth inhibition at 20  μ M. Compounds were also tested for their ability to inhibit leucine transport in LNCaP cells, and two analogues showed moderate activity with IC50 values of 8.9 and 8.5  μ M. This is the first reported synthesis of dihydro- β -agarofuran carbamate derivatives. Graphical abstract: Eight dihydro- β -agarofuran carbamate derivatives were synthesised and fully characterised, with absolute configurations assigned. Compounds were evaluated for their leucine uptake inhibition in the human prostate cancer cell line, LNCaP, and two analogues showed IC50 values of ~9 μM. Image 1 Highlights: Eight dihydro- β -agarofuran carbamate analogues were synthesised and characterised. Analogues were obtained in high purity (>95%) and variable yields (9–91%). The absolute configuration of one analogue was confirmed by X-ray analysis. Two analogues showed moderate inhibition of leucine uptake in the LNCaP cell line. This is the first reported synthesis of dihydro- β -agarofuran carbamate derivatives.